The State of the Art in Endodontics - Amato, Massimo; Pantaleo, Giuseppe; Iandolo, Alfredo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Nowadays, we use the term "modern endodontics" thanks to new technologies, novel materials, and revolutionary techniques. Various equipment is available to facilitate and improve our endodontic treatments, such as operating microscopes, ultrasounds, lasers, modern alloys for rotary files, powerful irrigation systems, new materials for filling root canals, 3D radiology, and several more. With the aid of the previously mentioned advances, complex endodontic treatments can be carried out safely, hence guaranteeing patients a high level of care and, above all, saving teeth that would otherwise be doomed for extraction. General practitioners and, even more importantly, specialists in endodontics should implement these modern technologies in their practice. This Special Issue will focus on modern endodontics regarding all the recent updates. Full papers of original articles, short communications, and review articles are all invited.